The Effect of Profitability, Retention Policy, and Tax Planning, on Firm Value with Financing Policy as A Moderating Variable - Mediaty; Muhammad Afdhal Usman; Abdul Hamid Habbe (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to explain and examine the effect of profitability, retention policy, and tax planning on firm value with financing policy serving as a moderating variable. The study's population and sample comprise companies categorized under LQ45 on the Indonesia Stock Exchange, during the timeframe spanning from 2015 to 2022. The research employs purpose sampling for sample selection and will utilize the methods of Moderated Regression Analysis. This research reveal that profitability and retention policy exert a positive and substantial influence, whereas tax planning does not affect the firm’s value significantly. Additionally, the financing policy does not moderate or weaken the influence of profitability, retention policy, and tax planning on firm value.